Direct Assessment of Cumulative Aryl Hydrocarbon Receptor Agonist Activity in Sera from Experimentally Exposed Mice and Environmentally Exposed Humans - Schlezinger, Jennifer J.; Bernard, Pamela L.; Haas, Amelia; Grandjean, Philippe; Weihe, Pal; Sherr, David H. (Environmental Health Perspectives, 2010)
BACKGROUND. Aryl hydrocarbon receptor (AhR) ligands adversely affect many biological processes. However, assessment of the significance of human exposures is hampered by an incomplete understanding of how complex mixtures affect AhR activation/inactivation. OBJECTIVES. These studies used biological readouts to provide a broader context for estimating human risk than that obtained with serum extraction and gas chromatography/mass spectroscopy (GC/MS)-based assays alone. METHODS. AhR agonist activity was quantified in sera from dioxin-treated mice, commercial human sources, and polychlorinated biphenyl (PCB)-exposed Faroe Islanders using an AhR-driven reporter cell line. To validate relationships between serum AhR agonist levels and biological outcomes, AhR agonist activity in mouse sera correlated with toxic end points. AhR agonist activity in unmanipulated ("neat") human sera was compared with these biologically relevant doses and with GC/MS-assayed PCB levels. RESULTS. Mouse serum AhR agonist activity correlated with injected dioxin dose, thymic atrophy, and heptomegaly, validating the use of neat serum to assess AhR agonist activity. AhR agonist activity in sera from Faroe Islanders varied widely, was associated with the frequency of recent pilot whale dinners, but did not correlate with levels of PCBs quantified by GC/MS. Surprisingly, significant "baseline" AhR activity was found in commercial human sera. CONCLUSIONS. An AhR reporter assay revealed cumulative levels of AhR activation potential in neat serum, whereas extraction may preclude detection of important non-dioxin-like biological activity. Significant levels of AhR agonist activity in commercial sera and in Faroe Islander sera, compared with that from experimentally exposed mice, suggest human exposures that are biologically relevant in both populations.